La filière AES, un renouvellement de la professionnalisation et de la démocratisation dans l'Université française ? - Sonia Lefeuvre (Les éditions de la Maison des sciences de l'Homme, 2011)
Is the professionalization of universities the answer to the larger question of education demand? Or is it a solicitation on the part of economic actors? The implementation of the economic and social administration (AES) course of study illustrates the creation of a vocational program. In the perspective of May 1968 and yet implemented under a right wing government in 1973, the AES project unites politically opposing actors. The common goal was to democratize education and adapt it to job opportunities (Prost, 1981). The underlying antagonism which exists between economical and individual concerns finds a shared answer here : on one hand, by seeing students' point of view and, on the other hand, by bring the concerns of the private sector to the forefront.